Dampak Sosial Ekonomi Alih Fungsi Lahan Perkotaan (Studi Kasus Pembangunan Jalan HOS Cokroaminoto Menjadi Kawasan Wisata) - Yessi Kumala Dewi; Sugeng Harianto (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
Land conversion is a change in the function of part or all of the land area from its previously determined function to another function. This study aims to determined the description of the location of land use change, to determine the factors of the occurrence of non-tourism land conversion into tourism, and to determine the impact of land conversion as a tourist area. In order to approach the problem, a reference to the theory of the struggle for urban spatial planning is used. The data were collected through interviews and literature studies which were analyzed qualitatively descriptively. The result of this study indicate that land use change has several economic and socio-cultural impacts. The economic impacts of the development of a night tourism area on the HOS Cokroaminoto road include: 1) increasing people’s income; 2) employment; and 3) opening up new business opportunities for the community. In addition to the economic impact, the development of a tourist area on HOS Cokroaminoto road has socio-cultural impacts, including: 1) becoming a means of preserving traditional culture. 2) provision of business land; and 3) the layout of the city becomes beautiful and neat. The construction of the HOS Cokroaminoto road also has a negative impact, including the number of visitors who exploded during the Covid-19 pandemic and the narrowing of the road area, due to the government widening the sidewalk area.Alih fungsi lahan merupakan sebuah perubahan fungsi dari sebagian ataupun keseluruhan kawasan lahan dari fungsinya yang sebelumnya telah ditentukan menjadi fungsi lain. Penelitian ini bertujuan untuk mengetahui gambaran lokasi alih fungsi lahan, untuk mengetahui faktor-faktor terjadinya alih fungsi lahan non-pariwisata menjadi pariwisata, serta untuk mengetahui dampak alih fungsi lahan sebagai kawasan wisata. Guna mendekati masalah, digunakan acuan teori perebutan tata ruang kota. Data-data dikumpulkan melalui hasil wawancara dan studi kepustakaan yang dianalisis secara kualitatif deskripitf. Hasil penelitian ini menunjukkan bahwa alih fungsi lahan memberikan beberapa dampak dalam segi ekonomi dan sosial-budaya. Dampak ekonomi dari adanya pembangunan kawasan wisata malam di Jalan HOS Cokrominoto antara lain: 1) meningkatkan pendapatan masyarakat; 2) penyerapan tenaga kerja; dan 3) membuka peluang usaha baru bagi masyarakat. Selain adanya dampak ekonomi, dengan pembangunan kawasan wisata di Jalan HOS Cokroaminoto memiliki dampak sosial-budaya, antara lain: 1) menjadi sarana pelestarian budaya tradisional; 2) penyediaan lahan usaha; dan 3) tata ruang kota menjadi indah dan rapi. Adanya pembangunan Jalan HOS Cokroaminoto juga memiliki dampak negatif, antara lain jumlah pengunjung yang membludak pada masa pandemi Covid-19 dan penyempitan luas jalan raya, dikarenakan pemerintah melakukan pelebaran pada area trotoar.